Sikap Petani terhadap Program Upsus Padi, Jagung dan Kedelai (Pajale) di Desa Kolisia B Kecamatan Magepanda Kabupaten Sikka - Akbar Saitama (Agriculture - Jurnal Ilmu Pertanian, 2025)
A study was conducted in Kolisia B Village, Magepanda District, Sikka Regency. The purpose of this study was to examine farmers' attitudes towards UPSUS PAJALE activities and to determine the factors that shape farmers' attitudes related to farmers' attitudes towards UPSUS PAJALE activities in Kolisia B Village, Magepanda District. The results of the study showed that farmers' attitudes including age, personal experience, formal education, non-formal education, the influence of others who are considered important and mass media in Kolisia B Village towards the UPSUS PAJALE program were classified as good. The relationship between attitude-forming factors and farmers' attitudes towards the UPSUS PAJALE program: there was a significant relationship between non-formal education and mass media accessed with farmers' attitudes towards the Special Efforts for Rice, Corn and Soybeans (UPSUS PAJALE) program in Kolisia B Village. There was an insignificant relationship between farmers' age, personal experience, formal education and the influence of others who were considered important with farmers' attitudes towards the Special Efforts for Rice, Corn and Soybeans (UPSUS PAJALE) program in Kolisia B Village.